Strategies for improving parents' self- efficacy and involvement in children’s school readiness (2016)
Readiness for school is a developmental task that involves adaptation for both parent and child which is being undertaken unconsciously. The ability of a child to cope and be competent at the point of school entry is embedded in early developmental experiences he/she is exposed to at home, and in the preschool environment. Lack of school readiness in preschool children is often identified as a cause of early academic failure and school misbehaviour, and it has been found to strongly predict employability difficulties, criminality and psychological morbidity as well as short-term academic problems. It is no gain saying that pre-school experience has positive impact on children's achievement in primary school. In addition to child readiness, good preschool programmes may also intentionally improve parental readiness for school through different teachers’ strategies as there is a controversy over how school readiness is being defined; that it cannot be defined as something which only resides in the child but also in the parents. How parents perceive themselves as capable enough to help their child’s readiness for school will determine how involved they would be in their child’s academic pursuit, thereby meeting the needs of the whole child. Research indicates that, some forms of parental involvement have a positive impact on children's academic success and teachers’ strategies are essential to the promotion of parent’s involvement.